Design considerations for wavefront sensing with self-referencing interferometers in adaptive optics systems - MacGillivray Alexander C.; Hristovski Ilija R.; Jenne Matthias F.; Reeves Andrew P.; Mata Calvo Ramon; Holzman Jonathan F. (Journal of the European Optical Society-Rapid Publications)
In this work, we show the design and implementation of wavefront sensing with a self-referencing interferometer (SRI). The SRI is developed to aid adaptive optics (AO) control, via deformable mirrors, in correcting wavefront error from atmospheric turbulence in (laser-based) free-space optical communication links. The SRI is used here given its potential to outperform more common wavefront sensors in functioning over weak through strong turbulence conditions. In this study, we identify and analyse the key parameters in the SRI’s optical design and show guiding principles for its subsequent image processing.